2012
DOI: 10.1016/j.talanta.2011.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Turbidimetric and photometric determination of total tannins in tea using a micro-flow-batch analyzer

Abstract: Both turbidimetric and photometric determinations of total tannins in samples of green and black tea, using a micro-flow-batch analyzer (μFBA) were studied. The miniaturized system was formed using photocurable urethane-acrylate resin and ultraviolet lithography technique. The turbidimetric method was based on the precipitation reaction of Cu (II) with tannins in acetate medium at a pH of 4.5. The photometric method was based on the complexation reaction of tannins with ferrous tartrate. The turbidimetric μFBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…Tannins are found in foods and beverages, especially in green and black tea. They confer acidity and astringency to wine and a variety of drinks [39,40]. Although the tannin content was not determined in this study, M. indica has been reported to contain gallotannins [41], suggesting that teas made from its leaves contain certain amounts of these compounds, which may be related to the acidity, astringency and bitterness of these beverages.…”
Section: Physicochemical Characterization Of the Teamentioning
confidence: 66%
“…Tannins are found in foods and beverages, especially in green and black tea. They confer acidity and astringency to wine and a variety of drinks [39,40]. Although the tannin content was not determined in this study, M. indica has been reported to contain gallotannins [41], suggesting that teas made from its leaves contain certain amounts of these compounds, which may be related to the acidity, astringency and bitterness of these beverages.…”
Section: Physicochemical Characterization Of the Teamentioning
confidence: 66%
“…We obtained a high speed of analysis, thanks to the optimizations in the addition times and volumes of the fluids, in a microsystem that allowed a homogenization efficient and discrete measurements. Although the proposed system has been applied only to samples of green tea, the ferrous tartrate method can be also applied, in the same DIB-μFBA, for other types of tea, such as black tea, oolong tea, and white tea, where the tannin may vary between 10 and 100 mg L −1 [26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…The ferrous tartrate method is more selective than the Folin-Ciocalteau method [25] and is unaffected by the coexistence of reducing agents, such as ascorbic acid [26]. It is being used by researchers for the spectrophotometric determination of tannins in tea [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of these compounds as shown in this study correlates to the significant antioxidant activity of the plant as reported earlier 18 . Tannins are a polyphenol group with high molecular weights and in general possess antioxidant, anticarcinogenic, antimutagenic and antimicrobial activities and it can also assist in the prevention and treatment of diseases 35 . Saponins are glycosides of both triterpenes and sterols and have rich pharmaceutical importance.…”
Section: Discussionmentioning
confidence: 99%